Emotion crafting: Individuals as agents of their positive emotional experiences - Van der Kaap-Deeder, J.; Wichstrøm, L.; Mouratidis, A.; Matos, L.; Steinsbekk, S. (Motivation and Emotion, 2023)
The literature on emotion regulation (ER) is vast and insightful, but little is known about the proactive regulation of positive emotions. Herein we coin the term emotion crafting (EC), which is defined as proactively aiming to strengthen one’s positive emotions through two sequential components: being aware of what can make one feel good (i.e., awareness component) and proactively engaging in behaviors to initiate, maintain, or increase positive emotions (i.e., action component). We present a self-report measure of EC [i.e., the Emotion Crafting Scale (ECS)] and provide details on its discriminant and concurrent validity. Data were collected among a sample of 326 Norwegian adults (49.7% female; Mage = 42.90 years, SD = 14.76) who were representative in terms of age (between 18 and 70), gender, and geographical location within Norway. Results yielded evidence for a 2-factor structure consisting of the components Awareness and Action, which related in an expected way to other measures of ER. Subsequent structural equation modeling showed that the awareness component related positively to indicators of well-being and negatively to internalizing symptoms via higher levels of EC action and positive affect, even after controlling for other measures of ER. These promising findings not only support favorable reliability and validity of the ECS, but also underscore the importance of examining proactive regulation of positive emotions as a potential predictor of mental health. Future research is needed to examine the etiological role of EC in individuals’ psychological functioning. © 2023, The Author(s).
Keywords: Broaden-and-Build Theory; Emotion crafting; Emotion regulation; Positive emotions; Self-determination theory